STUDI KOMPARASI FATWA MAJELIS ULAMA INDONESIA DAN FATWA JABATAN KEMAJUAN ISLAM MALAYSIA TENTANG HUKUM MAKANAN DAN MINUMAN BERALKOHOL - Haswin, Ferdy Hasan (Al-Usroh, 2024)
This study aims to study: 1) Comparison of MUI and Jakim Malaysia fatwas related to food and beverages containing alcohol; 2) The law of consuming the product is based on both fatwas. This study uses a qualitative method with a literature study approach. Data is obtained from journals, books, fatwas, and relevant news. Data analysis is carried out through reduction, presentation, and source verification, with the validity of the data guaranteed through member checks and source triangulation. The results of the study show that: 1) Fatwa MUI and Jakim Malaysia have differences in handling alcohol issues; 2) The law on consuming alcoholic products varies depending on the context and interpretation of each fatwa; This research is expected to provide a more comprehensive understanding for the public regarding this issue.